2019
DOI: 10.32479/ijefi.7626
|View full text |Cite
|
Sign up to set email alerts
|

Social Enterprise: The Alternatives Financial Support for Educational Institusion

Abstract: Enterprise social in the context of education is one of the innovations in maintaining the financial resources of an educational institution. In this study, social enterprise sustainability was used to realize a social enterprise-based boarding school management system, as well as supporting education improvement in Gontor Islamic Boarding School. This research method is action research to find out how the sustainability model of social enterprise implementation is carried out by Gontor. The results of the stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…The results of this study are in accordance with the findings of Siahaan, Iswati, & Zarkasyi, (2019); Sulaiman, Suswanto, & Masrukin, (2018) who concluded that there was a positive and significant effect jointly between the use of financial technology and economic education on the size of social impact. Utilization of good financial technology and Islamic economic education will be able to provide good social implications, especially on the welfare of the community.…”
Section: The Social Impact Of Financial Technology and Islamic Economic Educationsupporting
confidence: 92%
See 1 more Smart Citation
“…The results of this study are in accordance with the findings of Siahaan, Iswati, & Zarkasyi, (2019); Sulaiman, Suswanto, & Masrukin, (2018) who concluded that there was a positive and significant effect jointly between the use of financial technology and economic education on the size of social impact. Utilization of good financial technology and Islamic economic education will be able to provide good social implications, especially on the welfare of the community.…”
Section: The Social Impact Of Financial Technology and Islamic Economic Educationsupporting
confidence: 92%
“…Where human resources who have the ability in Islamic economics are needed to be able to drive the economic development of sharia towards the country's development. Preparing productive human resources through social entrepreneurship as an alternative financial support for Islamic economic education institutions (Siahaan, Iswati, & Zarkasyi, 2019;Sulaiman, Suswanto, & Masrukin, 2018) and having a good entitlement are certainly one of the keys to success in facing the challenge of uncertainty. in the midst of morality and socioeconomic crisis (Wahyudin, Rusdin, & Abdul, 2017).…”
Section: Basrowi Social Impact Of Financial Technology and Islamic Economics Educationmentioning
confidence: 99%
“…In the problems mentioned above, the author will examine issues that are considered very important to discuss, namely the assumption that Islamic boarding school leaders have not been able to solve all the challenges and weaknesses faced in facing the globalization era, namely: how is the management of leadership education in Islamic boarding schools in preparing their successor cadres after he died, to become the next leader whose character and leadership spirit will be the same or more competent, and be relied upon to have scientific insights and skills in the era of globalization (Siahaan et al, 2019), while still having ijtihad for his leadership which is a legacy , which continues and is practiced including the term heir (ahli waris) (Fauzi, 2019), in his administration and of course in the world of Islamic boarding schools the focus is not only on religious education which is occupied (Kurniawan, 2018), but related to national, social insights , politics, economics, society, and so on, not to mention the presence of kiai as religious leaders (D'Aiglepieree & Bauer, 2018); (Sila, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, due to a lack of funding and resources, many Indonesian Islamic educational institutions (pesantren) are at risk of collapsing; as a result, they require financial assistance to function effectively and to preserve its sustainability. According to Siahaan et al, (2019) the Indonesian government's budgetary is in the restrictions which do not only apply to Islamic institutions, are also the reason for this. These difficult economic conditions may make the instability of the pesantren worse.…”
Section: Introductionmentioning
confidence: 99%